Randomized in vivo trial evaluating plaque inhibition benefits of an advanced stannous‐containing sodium fluoride dentifrice used in conjunction with power brush technology. Issue 2 (12th July 2013) - Bellamy, PG; Boulding, A; Farmer, S; Day, TN; Barker, ML; Harris, R; Mussett, AJ
Abstract Objective To compare the plaque inhibition efficacy of a novel stannous‐containing sodium fluoride test dentifrice to a standard anticavity negative control dentifrice, when both were used in conjunction with an advanced oscillating–rotating (O/R) power toothbrush. Methods This was a randomized, two‐treatment, three‐period, double‐blind crossover study conducted in a population using an O/R power brush. Subjects brushed twice per day with their assigned dentifrice during the three‐treatment periods, each lasting for 17 consecutive days. Each period was separated by a 4‐day washout period during which subjects continued to use their O/R power toothbrush. Plaque levels were assessed and averaged amongst three assessments taken on days 15, 16 and 17 at the end of each treatment period using digital plaque imaging analysis. Assessments were carried out on the facial anterior tooth surfaces in the morning before brushing (A.M. prebrush) following whole‐mouth brushing (30 s per quadrant) with the assigned dentifrice (A.M. post‐brush) and in the afternoon (P.M.). Results Twenty‐seven subjects were randomized and completed the study. During the 17‐day usage period, the stannous‐containing test NaF dentifrice demonstrated a statistically significant lower mean plaque area versus the negative control dentifrice at each assessment timepoint; overnight A.M. prebrush was 33.8% lower (P < 0.0001), A.M. post‐brush was 21.8% lower (P < 0.01), and P.M. was 29.2% lower (P < 0.0001). Conclusion A population of O/R power toothbrush users had significantly less plaque coverage for all three measurements when using a stannous‐containing NaF dentifrice than when using a negative control (fluoride) dentifrice.